The Effect of Informational and Emotional Support Program on Uncertainty in Illness among Mothers having Children with Intubation - Petchlek, Pennapa; Teerarungsikul, Narumon; Sananreangsak, Siriyupa (Princess of Naradhiwas University Journal, 2019)
Mothers with a child have been given a intubated will have an unstable feeling in the illness. Should be social support, informational and emotional. To make the feeling of uncertainty decrease.This quasi-experimental research aimed to examine effect of informational and emotional support program on uncertainty in illness among mothers having children with intubation. Participants were 30 mothers of children with intubation admitted to the PICU, Trang Hospital. They were divided equally into either the control (n=15) or experimental group (n=15). The control group received routine care. The experimental group received the informational and emotional support program. Research instruments consisted of the questionnaire general information of mothers and children and the Mothers Perception of Uncertainty questionnaire. Their Cronbach’s alpha was .82. Data were analyzed by descriptive statistics, Independent t-test and paired t-test. The result revealed that after the experiment, the mean score of mothers, uncertainty in the experimental group were significantly lower than those in the control group (p < .001) and lower than before receiving the program (p < .001). The finding show that the informational and emotional support program can help reduce uncertainty in mothers of children with intubation.